A Delphi study on research priorities in radiation therapy: The Norwegian perspective - Egestad, H.; Halkett, Georgia (W.B. Saunders Ltd, 2015)
Introduction: Although radiation therapists (RTs) need to engage more in research to establish an evidence base for their daily practice the majority conduct little research themselves. This project is the second stage of a Delphi process aimed at determining research priorities in radiation therapy in Norway. The aim of this article is to prioritize the research areas radiation therapists in Norway think are most important in their own profession. Methods: A questionnaire was administered using responses to a previous questionnaire, which identified the research interests of Norwegian RTs. The survey was sent to all Norwegian departments of radiation oncology, and RTs were asked to form interest groups to discuss and prioritize the research areas. Results: There was a 70% response rate, seven of 10 departments participated. The highest ranked research categories were imaging in radiation therapy and radiation therapist education. Seven of the top ten ranked research areas were in these categories. Conclusion: Prioritization of research areas and categories provides a useful list of future research for Norwegian RTs, which will enable them to decide whether their research ideas are a high priority, and spend less time deciding on a relevant research topic that needs investigation in their own workplaces.